Sosialisasi Edukatif dalam Meningkatkan Kesadaran Remaja terhadap Bahaya Narkoba dan Minuman Keras di SMP Negeri 3 Kombeng - Azmia Azmia; Fitriani Fitriani; Asnah Asnah; Anggra Prima (MAYARA: Jurnal Pengabdian Masyarakat, 2026)
Drug abuse and alcohol consumption remain critical issues affecting adolescents’ physical, psychological, and social well-being. This community service activity aimed to enhance students’ understanding and awareness of the dangers of drugs and alcohol through an interactive educational outreach approach. The method employed was a descriptive qualitative approach with participatory techniques, including observation, interactive discussions, and evaluation of participants’ responses. The activity was conducted at SMP Negeri 3 Kombeng involving 191 students. The results indicated an improvement in students’ understanding, reflected in increased active participation, the ability to explain the negative impacts of drug and alcohol abuse, and a shift in attitudes from permissive to preventive behavior. These findings demonstrate that interactive educational outreach is an effective preventive strategy in fostering adolescents’ awareness within the school environment.